Pengaruh Bauran Pemasaran Jasa dan Kepercayaan Terhadap Loyalitas Konsumen di Hotel Axana Padang - Arfi, Nadila; Chandrayanti, Teti; Yulistia, Yulistia (Ekasakti Matua Jurnal Manajemen, 2024)
This study aims to examine and analyze the dominant indicators of the service marketing mix and trust on customer loyalty, the effect of the service marketing mix (products, participants, physical environment) on customer loyalty, participants/persons on customer loyalty, and the effect of trust on customer loyalty. the influence of the service marketing mix and trust simultaneously on consumer loyalty. This study uses the classic assumption test which consists of the normality test, multiculeority test, heroscadicity test and multiple regression test, t test and F test. participant indicators increase living rates, physical environment equipment indicator trust Integrity and consumer loyalty indicators cooperation indicators, products have a positive and not significant effect on consumer loyalty, participants have a positive and insignificant effect on consumer loyalty, the physical environment has a positive and significant effect on consumer loyalty, trust has a positive and significant effect on customer loyalty, service marketing mix (products, participants, physical environment) and consumer trust has a positive and significant effect on customer loyalty at the Axana Hotel Padang and the coefficient of determination (R2) is 0.962 where KD = r² x100% or KD = 0.962 x 100% = 96.20%. This 96.20% value shows the effect of the independent variable on the dependent variable and the remaining 3.80% is influenced by other factors such as promotions, service quality, consumer decisions and consumer satisfaction.